The Dogmas of the Technical Translation - Are They Still Valid? - Zethsen, Karen Korning (HERMES - Journal of Language and Communication in Business, 1999)
Technical texts are generally considered to be informative, objective and devoid of expressive features. In this paper I shall argue in favour of the more recent assertion that technical texts are not only concerned with the transfer of facts, but - like texts in general - serve various communicative purposes. The aim of my work is to increase the awareness of the translation scholar and the professional translator of the fact that literary texts do not hold a monopoly on expressivity and creativity and that also within the framework of technical translation the expressive function must be expected, noticed and translated. I shall furthermore argue that “technical texts” do NOT constitute a genre - on the contrary a great variety of genres make use of technical language.